The Core International Human Rights Treaties (United Nations New YorkUS, 2014)
This publications seeks to make accessible human rights treaties to State officials, civil society organisations, human rights defenders, legal practictioners, scholars, individual rights holders and others with an interest in human rights norms and standards.
Keywords: HUMAN RIGHTS